FACTORS AFFECTING THE PERFORMANCE OF LIBRARY AND INFORMATION PROFESSIONALS IN THE LIBRARIANS' LICENSURE EXAMINATION (LLE) 2006-2010, PART 2: YEAR OF GRADUATION, ACADEMIC DEGREES, AND EDUCATIONAL INSTITUTIONS - Ramos, Mila; Ananoria, Arabella; Nera, Corazon (Journal of Philippine Librarianship; Vol 33 No 1 (2013))
This article presents factors such as year of graduation, academic degrees, and educational institutions, that affect the performance of the LLE takers for the years 2006-2010. These factors were then correlated with the passing percentage for the years 2005-2010. It was found out that all these factors do not significantly affect performance in LLE.
Keywords: library and information science, LIS, licensure examination, philippine librarianship, professional regulation commission